2021
DOI: 10.5398/tasj.2021.44.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive Value and Preference of Guinea-Grass Ensiled with or without Additive by West African Dwarf (WAD) Goats

Abstract: A study was designed to investigate silage additives’ effect on preference and nutritive value of five weeks re-growth guinea grass by West African dwarf (WAD) goats. The silages of five weeks re-growth guinea grass were made without additive (T1), with cassava peels additive (T2), and with fermented epiphytic juice of lactic acid bacteria in Panicum maximum (FEJPM) additive (T3). The effects of silage additives on preference, voluntary feed intake, growth, digestibility, and nitrogen utilization were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
(34 reference statements)
2
0
2
Order By: Relevance
“…The saponins contents from this study ranged from 11-21mg/100g in all diet. These values were slightly similar to 9-13mg/100g reported by Abegunde et al (2021). The concentration of saponin in this study is still within tolerable level of 1.5 -2% (Onwuka, 1983).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The saponins contents from this study ranged from 11-21mg/100g in all diet. These values were slightly similar to 9-13mg/100g reported by Abegunde et al (2021). The concentration of saponin in this study is still within tolerable level of 1.5 -2% (Onwuka, 1983).…”
Section: Discussionsupporting
confidence: 90%
“…These anti-nutrients also play role in defense mechanism in plants by producing tannin. Levels of antinutrients reported in this study was lower compared with the study of Abegunde et al (2021) whose value were below the threshold levels permissible in ruminant animals (Umar et al, 2014).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This view is supported by Ahamefule et al (2001) who earlier reported that higher protein content of diet has significant effect on Nintake of dwarf sheep. The values reported for nitrogen intake in this study are lower than those reported by Abegunde et al (2021) for WAD goats fed ensiled Guinea grass (7.19-12.41 g/d) but were higher than those reported by Mako et al (2012) for WAD goats fed guinea grass and varying levels of Acroceras zizanioides (AZ) (3.85 -6.95 g/d).…”
Section: Chemical Composition Of Elephant Grass (Pennisetum Purpureum...contrasting
confidence: 84%